2019
DOI: 10.1186/s40659-019-0218-7
|View full text |Cite
|
Sign up to set email alerts
|

IRF2–INPP4B-mediated autophagy suppresses apoptosis in acute myeloid leukemia cells

Abstract: BackgroundThe present study aimed to investigate the underlying role of interferon-regulatory factor 2 (IRF2)–inositol polyphosphate-4-phosphatase, type-II (INPP4B) axis in the regulation of autophagy in acute myeloid leukemia (AML) cells.MethodsQuantitative real time PCR (QRT-PCR) and western blot were performed to determine the expression levels of IRF2, INPP4B and autophagy-related markers in AML cell lines. Autophagy was assessed by elevated Beclin-1 expression, the conversion of light chain 3 (LC3)-I to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…IRF proteins play pivotal roles in regulating immune response, lymphocyte differentiation, hematopoietic stem cell development and cell proliferation and tumorigenesis [8] . Among this family, IRF2 is associated with the development of various cancers by regulating gene transcription, such as TP53, CXCL3, Bcl-2, and Bax [9] , [10] , [11] . IRF2 is upregulated in pancreatic cancer and HCC cells, and high levels of IRF2 are associated with a worse feature of tumor infiltration depth [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…IRF proteins play pivotal roles in regulating immune response, lymphocyte differentiation, hematopoietic stem cell development and cell proliferation and tumorigenesis [8] . Among this family, IRF2 is associated with the development of various cancers by regulating gene transcription, such as TP53, CXCL3, Bcl-2, and Bax [9] , [10] , [11] . IRF2 is upregulated in pancreatic cancer and HCC cells, and high levels of IRF2 are associated with a worse feature of tumor infiltration depth [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for decreased CR of patients with high INPP4B expression is that overexpression leads to increased colony forming potential and increased proliferation in AML cell lines (10) . INPP4B overexpression provide the cell a growth advantage, in part by decreased basal apoptotic activity (27) . Also, overexpression in AML cells leads to decreased sensitivity to DNA and ionizing radiation because INPP4B has a direct role in chemotherapy response and is important in mediating cellular response to DNA damaging agents as reported by Dzneladze et al (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, IRF2 might regulate cell autophagy by interacting with INPP4B, and facilitating the development of AML. So, IRF2-INPP4B axis inhibited the apoptosis of AML cells via inducing autophagy in vitro, and thus could be a new target for gene therapy in AML (27) . Accordingly, we assessed the effect of INPP4B overexpression on the treatment outcome and survival in denovo AML patients.…”
Section: (11)mentioning
confidence: 98%
“…Previous studies suggested that INPP4B is involved in the apoptosis of tumor cells [15,30]. The apoptosis levels of different lentivirus infection GBC-SD and SGC-996 cells were analysed by ow cytometry.…”
Section: Inpp4b Regulates Gbc Cells Apoptosis In Vitromentioning
confidence: 99%